Fiberoptic Endoscopic Evaluation of Swallowing: A Multidisciplinary Alternative for Assessment of Infants With Dysphagia in the Neonatal Intensive Care Unit. (February 2016) - Reynolds, Jenny; Carroll, Sandra; Sturdivant, Chrysty
Abstract : Background: The standard procedure to assess an infant in the neonatal intensive care unit (NICU) who is suspected of aspirating on oral feedings is a videofluoroscopic swallowing study (VFSS). The VFSS has been used for more than 30 years to assess dysphagia and is considered the gold standard. However, there are challenges to the VFSS, including radiation exposure, transport to radiology, usage of barium, limited positioning options, and cost. An alternative approach is fiberoptic endoscopic evaluation of swallowing (FEES), which uses a flexible endoscope passed transnasally into the pharynx to assess anatomy, movement/sensation of structures, swallow function, and response to therapeutic interventions. Fiberoptic endoscopic evaluation of swallowing has been established as a valid tool for evaluating dysphagia and utilized as an alternative or supplement to the VFSS in both adults and children. Purpose: This article provides an overview of the current challenges in the NICU with assessing aspiration and introduces a multidisciplinary FEES program for bottle and breastfeeding. Methods/Search Strategy: A review of the literature of dysphagia, VFSS, and FEES in the adult, pediatric, infant, and neonatal populations was performed. Clinical competency standards were researched and then implemented through an internal process of validation. Finally, a best practice protocol was designed as it relates to FEES in the NICU. Findings/Results: Fiberoptic endoscopic evaluation of swallowing is a safe alternative to the VFSS. It can be utilized at the infant's bedside in a NICU for the diagnosis and treatment of swallowing disorders by allowing the clinician the ability to replicate a more accurate feeding experience, therefore, determining a safe feeding plan. Implications for Practice: Competency and training are essential to establishing a multidisciplinary FEES program in the NICU. Implications for Research: Further research is needed to compare the efficacy and validity of FEES versus VFSS for infants in the NICU. Furthermore, evaluating the efficacy of FEES during breastfeeding is warranted.